Buckling analysis of FML cylindrical shells under combined axial and torsional loading - Ahmad Reza Ghasemi; Sina Kiani; Ali Tabatabaeian (Mechanics of Advanced Composite Structures)
Generally, in-served cylindrical shells buckling usually takes place not merely under one of the basic loads, i.e., axial compression, lateral pressure, and torsion, but under a combination of them. The buckling behavior of fiber-metal laminate (FML) cylindrical shells under combined axial and torsional loading is studied in this paper. The Kirchhoff Love-type assumption is employed to study the axial buckling load. Then, an extended finite element (FE) model is presented and results are compared. A number of consequential parameters such as lay-up arrangement, metal type and metal volume fraction are employed and enhancement of buckling behavior of the shell is also studied. Finally, the interaction of axial /torsional loading is analyzed and discussed. The results show that as the metal volume fraction rises to 15%, the endurable buckling load increases almost 43% more than the state in which there is no metal layer. The numerical results show that increasing the metal volume percentage leads to a decrease in buckling performance of the structure under axial loading.